PENGARUH IKLAN, MEDIA SOSIAL, DAN BRAND AMBASADOR TERHADAP BRAND EQUITY PADA BRAND SOMETHINC - Sajidha, Anggun (Universitas Nusantara PGRI Kediri, 2024)
This study investigates the increased usage of cosmetic products in Indonesia, reflecting a growing lifestyle trend. The rise in the number of cosmetic users presents opportunities for local producers to compete in a broad and diverse market. To gain a competitive edge, developing strong brand equity is crucial. This research aims to analyze the impact of advertising, social media, and brand ambassadors on brand equity, both partially and simultaneously, among Somethinc brand customers. Utilizing a quantitative approach with descriptive methods and Non-Probability Sampling techniques, the results indicate that advertising (X1) and social media (X2) significantly influence brand equity, while brand ambassadors (X3) do not have a significant partial impact. However, advertising, social media, and brand ambassadors collectively have a significant effect on the brand equity of Somethinc customers.